Comparison of Human Articular Cartilage Tissue and Chondrocytes Isolated from Peripheral versus Central Regions of Traumatic Lesions. (December 2021) - Acevedo, Lina; Iselin, Lukas; Berkelaar, Majoska H. M.; Salzmann, Gian M.; Wolf, Francine; Feliciano, Sandra; Vogel, Nicole; Pagenstert, Geert; Martin, Ivan; Pelttari, Karoliina; Barbero, Andrea; Arnold, Markus P.
Objective: Cellular and molecular events occurring in cartilage regions close to injury are poorly investigated, but can possibly compromise the outcome of cell-based cartilage repair. In this study, key functional properties were assessed for cartilage biopsies collected from the central part of traumatic joint lesions ( central ) and from regions surrounding the defect ( peripheral ). These properties were then correlated with the quality of the initial cartilage biopsy and the inflammatory state of the joint. Design: Cartilage samples were collected from knee joints of 42 patients with traumatic knee injuries and analyzed for cell phenotype (by reverse transcriptas-polymerase chain reaction), histological quality, cellularity, cell viability, proliferation capacity, and post-expansion chondrogenic capacity of chondrocytes (in pellet culture). Synovium was also harvested and analyzed for the expression of inflammatory cytokines. Results: Cartilage quality and post-expansion chondrogenic capacity were higher in peripheral versus central samples. Differences between these 2 parameters were more pronounced in joints with high inflammatory features characterized by >100-fold difference in the mRNA levels of IL6 and IL8 in the corresponding synovium. Peripheral chondrocytes isolated from good- versus bad-quality biopsies expressed higher levels of collagen II/I and aggrecan/versican and lower levels of MMP13 and ADAMTS5. They also exhibited reduced proliferation and enhanced cartilage-forming capacity. Conclusions: Chondrocytes at the periphery of traumatic lesions better maintain properties of healthy cartilage compared to those isolated from the center, even when derived from bad-quality tissues harvested from highly inflamed joints. Future studies are necessary to investigate the change of functional properties of peripheral chondrocytes over time.